Childhood maltreatment, pubertal development, HPA axis functioning, and psychosocial outcomes: An integrative biopsychosocial model. Issue 8 (11th September 2015) - Negriff, Sonya; Saxbe, Darby E.; Trickett, Penelope K.
ABSTRACT: The timing and pace of pubertal development has been associated with psychosocial functioning, with pubertal variables represented both as predictors (e.g., earlier puberty linked with poor outcomes) and as sequelae (e.g., early stress linked with earlier puberty). However, the literature has largely not tested mediational models or prospective mechanisms of associations between puberty and psychosocial variables. In a longitudinal study including 454 youth followed over four timepoints (mean ages 10–18), structural equation modeling tested a hypothesized path from childhood maltreatment to cortisol (Time 1) to pubertal stage (Time 2), and psychosocial outcomes (Times 3 and 4). There was not support for the full hypothesized pathway in either gender. However, for boys, maltreatment was associated with attenuated cortisol, and more pubertal change predicted subsequent delinquency. For girls, cortisol predicted more pubertal change which then predicted substance use. This study demonstrates links between HPA axis function, pubertal development, and risky outcomes. © 2015 Wiley Periodicals, Inc . Dev Psychobiol 57: 984–993, 2015.